Implementasi TOPSIS Pada Sistem Rekomendasi Tempat Wisata Dalam Kota Malang Berbasis Lokasi - Ricky Irfandi; Ratih Kartika Dewi; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Malang is the second-largest city in East Java, which is known as the tourism city because it has many interesting tourist destinations. However, many choices of tourist destinations in Malang confuse the tourists about choosing suitable tourism according to their wishes because of the limited funds and time. To overcome this problem, a mobile-based application is needed for decision-making that can provide tourist recommendations, so that tourists are expected to get travel recommendations that match their desired criteria from anywhere and anytime. The system developed based on Android so it can be used by a wide range of users. The system was built using the TOPSIS method to rank tourist recommendations according to the criteria entered by users based on tourist data provided by web services. The system has successfully fulfilled the functional requirements with a valid value of 100% on functional testing. Besides, the validation testing of algorithms which is done by comparing the results of recommendations with manual calculations and the calculation of the system gets a 100% match. And for accuracy testing by experts gets an accuracy value of 83.3%.